TINGKAT KESEHATAN BANK DAN STRUKTUR MODAL TERHADAP RETURN SAHAM - Ahmad Yani; Intan Zulinda Santosa (Universitas Pakuan, 2020)
This study aims to examine the effect of bank health and capital structure on stock returns in banking companies. The research population is all banking companies listed on the Indonesia Stock Exchange in 2015-2017. The research sample was selected using purposive sampling method in order to obtain 11 banking companies. The data analysis used multiple linear regression analysis. The results showed that the indicators of bank health, namely the risk profile, income, and capital as well as capital structure (leverage) have an influence on stock returns. In addition, indicators of good corporate governance as an indicator of bank health have no effect on stock returns. The health bank needs the attention of the management as its responsibility in improving the company in order to obtain high stock returns. The better the health level of the bank, the higher the stock return will be.